Effectiveness of percutaneous posterior tibial nerve stimulation for the management of bowel dysfunction in multiple sclerosis patients. (September 2021) - Sacco, Rosaria; Braga, Andrea; Disanto, Giulio; Digesu, Giuseppe Alessandro; Maino, Paolo; Koetsier, Eva; Caccia, Giorgio; Serati, Maurizio; Renard, Julien; Gobbi, Claudio; Zecca, Chiara
Background: Neurogenic bowel dysfunctions (NBDs) in the form of both fecal incontinence (FI) and functional constipation (FC) are frequent in multiple sclerosis (MS) patients and significantly affect their quality of life. Therapeutic options are limited. Objective: To investigate effectiveness of percutaneous posterior tibial nerve stimulation (PTNS) in MS patients suffering from FI and FC. Methods: Prevalence and severity of FI and FC were prospectively collected among MS patients undergoing 12 weeks of PTNS for neurogenic bladder. The Cleveland Clinic Fecal Incontinence Score (CCFIS) and the Rome III criteria were used to define FI and FC, respectively. Subjective treatment satisfaction was estimated using the Benefit Satisfaction and Willingness to Continue (BSWC) questionnaire. Results: A total of 60 patients undergoing PTNS suffered from NBDs (25 FI+/FC+, 5 FI+/FC–, 30 FI–/FC+). Median CCFIS decreased after PTNS from 12.0 (11.0–13.0) to 8.5 (7.0–11.0, p < 0.001), with particular improvements in liquid and flatal incontinence, pads' need, and lifestyle restrictions. Seven patients became FC free after PTNS and no patients developed FC during the study ( p = 0.023). More than 50% of the patients were satisfied and willing to continue PTNS at study end. Conclusion: PTNS represents a valid minimally invasive alternative treatment for MS patients suffering from NBDs.